Control of the crystal habit and magnetic properties of Co nanoparticles through the stirring rate. Issue 25 (14th June 2017) - Mrad, K.; Schoenstein, F.; Nong, H. T. T.; Anagnostopoulou, E.; Viola, A.; Mouton, L.; Mercone, S.; Ricolleau, C.; Jouini, N.; Abderraba, M.; Lacroix, L.-M.; Viau, G.; et al.
Abstract : The morphological, structural and magnetic properties of hcp Co anisotropic nanocrystals can be tuned through mechanical agitation intensity. Abstract : Ferromagnetic hcp cobalt nanoparticles (NPs) are prepared by the polyol process using long-chain carboxylates as shape-directing agents, applying different stirring rates during the synthesis. Particles prepared with a stirring rate lower than ca. 150 rpm are very well-defined anisotropic crystals with smooth lateral facets and low stacking fault densities. The growth proceeds along the c axis of the hcp structure which corresponds to the long axis of the anisotropic particles. Increasing the stirring speed leads to a lowering of the mean aspect ratio, an increase in structural disorder as well as to a strong modification of the particle habit. The resulting Co NPs then display a marked surface roughness. We propose here a mechanism to explain the different morphologies observed. A high stacking fault density triggers the local disorganisation of the adsorbed capping agent layer which in turn favours the diffusion of Co monomers through the organic layer, resulting in the formation of excrescences perpendicular to the long axis of the particles. The magnetic properties are strongly related to the morphological and micro-structural properties of the particles. The stirring rate appears, so far, as the driving force to control the magnetic properties of the NPs from hard magnetic behaviour at low stirring rates to an almost soft magnetic one under high stirring conditions.